2020
DOI: 10.3390/pharmaceutics12100990
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Antitumor Immunity Contributes to the Overall Antitumor Effect of Pegylated Liposomal Doxorubicin (Doxil®) in C26 Tumor-Bearing Immunocompetent Mice

Abstract: Doxorubicin (DXR) has been reported to have direct cytotoxicity against cancer cells and indirect immunotoxicity by modulation of host antitumor immunity. Hence, it may prevent cancer progression by a dual mechanism. Doxil®, a formulation of DXR encapsulated in polyethylene glycol modified (PEGylated) liposomes, is the most widely used of the clinically approved liposomal anticancer drugs. However, the effect of Doxil® on host antitumor immunity is not well understood. In this study, Doxil® efficiently suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
(64 reference statements)
1
1
0
Order By: Relevance
“…The effect of pegylated liposomal doxorubicin on the immune system is of particular interest, as doxorubicin has been shown to have a direct cytotoxic effect on cells and a second indirect immunotoxic effect on the host-antitumor immunity. A recent pre-clinical study suggested that pegylated liposomal doxorubicin is more active in the presence of T cells, suggesting that this immune effect is also important for this drug 36. In this context the impact seen in our study of the neutrophil/lymphocyte ratio could be related to the exposure of the patients to pegylated liposomal doxorubicin.…”
Section: Discussionsupporting
confidence: 50%
“…The effect of pegylated liposomal doxorubicin on the immune system is of particular interest, as doxorubicin has been shown to have a direct cytotoxic effect on cells and a second indirect immunotoxic effect on the host-antitumor immunity. A recent pre-clinical study suggested that pegylated liposomal doxorubicin is more active in the presence of T cells, suggesting that this immune effect is also important for this drug 36. In this context the impact seen in our study of the neutrophil/lymphocyte ratio could be related to the exposure of the patients to pegylated liposomal doxorubicin.…”
Section: Discussionsupporting
confidence: 50%
“…Each liposome was intravenously injected at a dose of 5 mg DOX/kg because the intravenous injection of free DOX solution at 5 mg/kg did not provide any therapeutic effects against several types of cancers including B16-BL6. [27][28][29][30] L-Mid provided a significant and remarkable anti-tumor effect, while other liposomes did only a partial anti-tumor effect. Tumor growth rates during the early (0-11 days) and late (12-21 days) periods indicate that all the three preparations significantly suppressed the tumor growth in the early period, but only L-Mid provided a significant decrease of tumor growth rate during the late half, compared with the saline-treated control (Table 1).…”
Section: Resultsmentioning
confidence: 92%